2009
DOI: 10.1007/s00415-009-5290-4
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible spongiform encephalopathies with P102L mutation of PRNP manifesting different phenotypes: clinical, neuroimaging, and electrophysiological studies in Chinese kindred in Taiwan

Abstract: A P102L point mutation in the prion protein gene (PRNP) usually causes Gerstmann-Sträussler-Scheinker disease (GSS), which is a rare hereditary transmissible spongiform encephalopathy (TSE). The clinical features include ataxia in 50s age group with subsequent dementia, spastic paraparesis and extrapyramidal signs. Many families have been reported from the Caucasian population, but only one from the Chinese. We hereby report a large Chinese family with P102L mutation of PRNP whose clinical manifestations at on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…The most common clinical phenotype includes early ataxia with gait disturbances, sensory involvement in the lower extremities, and late cognitive decline, whereas visual disturbances, dystonia, and myoclonus are uncommon …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common clinical phenotype includes early ataxia with gait disturbances, sensory involvement in the lower extremities, and late cognitive decline, whereas visual disturbances, dystonia, and myoclonus are uncommon …”
mentioning
confidence: 99%
“…The first step was to retrospectively analyze the clinical manifestation and results from auxiliary diagnostic methods (ie, brain magnetic resonance imaging [MRI], electroencephalogram [EEG], and cerebrospinal fluid [CSF] analysis) in the 7 Czech cases with postmortem confirmation. The next step was to extend this analysis by combining the data from the 7 Czech patients with data from 87 previously published P102L GSS cases, and with the use of cluster analysis, to define typical GSS syndrome phenotypes.…”
mentioning
confidence: 99%
“…The main clinical, imaging, and laboratory findings of P102L mutations described in the literature are summarized in Table 2. Cognitive decline is typically present, but is usually mild and occurs later in the evolution of the disease (Cagnoli et al, 2008;Kovács et al, 2002;Park et al, 2010;Takazawa et al, 2010;Young, Clark, Piccardo, Dlouhy, & Ghetti, 1997); although, GSS P120L cases with cognitive decline, as one of the prominent symptoms, have been reported (Barbanti et al, 1996;Chi et al, 2010; Downloaded by [Florida Atlantic University] at 20:04 17 November 2014 Giovagnoli et al, 2008;Majtényi et al, 2000;Park et al, 2010;Webb et al, 2008). Cognitive decline, if present, often develops late in the course of the disease, seldom manifests as prominent dementia and is usually not accompanied by behavioral and psychiatric symptoms such as paranoia, delusions, and severe anosognosia.…”
Section: Discussionmentioning
confidence: 97%
“…Hyporeflexia or absence of deep tendon reflexes; extrapyramidal signs and spasticity in the lower extremities (Arata et al, 2006;Kovács et al, 2002, c 2005) are often reported. Painful dysesthesias can also occur (Arata et al, 2006;Yamada et al, 1999), while visual disturbances, dystonia and myoclonus are uncommon in GSS (Chi, Lee, Lu, Wu, & Soong, 2010). Other manifestations are rare; associations with ataxia, dementia and peripheral involvement including fasciculations, fibrillations, and amyotrophy (Kretzschmar et al, 1992) and a phenotype similar to progressive supranuclear palsy (A133V mutation) (Rowe et al, 2007) have been described.…”
mentioning
confidence: 96%
“…Those clinicogenotypic results also provide no linkages between genotypes and clinical expressions. Loss of muscle stretch reflexes was described in two of 7 patients (6). As compared to heterogeneous phenotypes in Japanese families (4,7,8), British families (3), an Italian family (5), a Chinese family (6) and an original Austrian kindred (10) …”
Section: Austrian England British-canadian French German Italianmentioning
confidence: 99%